2017
DOI: 10.1111/adj.12494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tooth bleaching on dental enamel microhardness: a systematic review and meta‐analysis

Abstract: Several studies have investigated the effect of bleaching on dental tissues. The evaluation of the effect of home bleaching with 10% carbamide peroxide is important for assessing alterations in enamel microhardness that may affect dental health in terms of resistance to masticatory forces. This meta-analysis was performed in order to determine scientific evidence regarding the effects of home vital bleaching with 10% carbamide peroxide gel on the microhardness of human dental enamel. A systematic electronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 26 publications
1
35
0
10
Order By: Relevance
“…16–18 In addition, the use of CPP–ACP paste together with fluoride has been reported to encourage the passage of F - ions together with calcium and phosphate ions, and to have a synergistic effect, hence increasing remineralization. 19 Rehder Neto et al 14 and Turssi et al 19 evaluated the remineralization efficacy of toothpastes containing CPP–ACP and CPP–ACPF with a microhardness test and reported that surface hardness was increased following remineralization in their experimental groups, although the hardness values were similar between the groups. In the same study, similar to the findings of more recent studies, no statistically significant differences were found in the microhardness values of the CPP–ACP, CPP–ACPF, and NaF groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16–18 In addition, the use of CPP–ACP paste together with fluoride has been reported to encourage the passage of F - ions together with calcium and phosphate ions, and to have a synergistic effect, hence increasing remineralization. 19 Rehder Neto et al 14 and Turssi et al 19 evaluated the remineralization efficacy of toothpastes containing CPP–ACP and CPP–ACPF with a microhardness test and reported that surface hardness was increased following remineralization in their experimental groups, although the hardness values were similar between the groups. In the same study, similar to the findings of more recent studies, no statistically significant differences were found in the microhardness values of the CPP–ACP, CPP–ACPF, and NaF groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect mineral losses or gains can be determined through a microhardness analysis method, the suitability of which has been demonstrated based on quantitative information on the mineral changes that occur to the enamel surface, and its status as a repeatable, fast, and easily applicable process. 14,15 Many in vitro studies to date have demonstrated that CPP–ACP compounds dissolve in an acidic environment and increase the saturation and activity of calcium and phosphate ions in plaque. Accordingly, an oversaturated environment has been reported to prevent demineralization and to support remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been hypothesized that, after tooth bleaching, teeth could be more prompt to plaque accumulation due to surface modifications . Although tooth bleaching seems to have a minimum or no effect on enamel hardness and mineral content, the results are inconsistent . Enamel surface alterations may vary according to the whitening products used and seem to be associated to the use of bleaching agents with a low pH.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that fractional CO2 laser following absorption, there would be a high temperature increase in the surface and near the surface enamel layers, which results in structural and chemical alterations of enamel including decomposition of organic matrix, reduction of carbonate content, and fusion and recrystallization of hydroxyapatite crystals ( 8 , 15 , 16 ) N-HA and MI paste enhance the remineralization of enamel surface, which had been demineralized after tooth bleaching ( 8 , 17 ). Nano-hydroxyapatite enhances remineralization of enamel surfaces by occluding the surface microporosities, which results in prevention stain absorption and increasing surface microhardness ( 18 ). Very few studies have been done on the effect of post bleaching treatment on elastic modulus of enamel.…”
Section: Discussionmentioning
confidence: 99%